A history of the growth of the shipping industry and the development of the port area of Cebu before the American era - Rubia, Roquezon O. (2007)
This paper shall attempt to identify and narrate the contributory factors that led to the growth of the shipping industry and the development of the port area of Cebu before the American era. It provides a brief background of Cebu?s traditional role as an important entrepot from its pre-Hispanic days, its decline during the Spanish rule, and its eventual rejuvenation during the latter part of the Spanish Period. The paper also attempts to prove that the growth of the shipping industry in Cebu went hand in hand with the physical development of the port area and the city itself.
Includes bibliographical references (pages 280-284).